Fluorescence-guided laparoscopic living-donor hepatectomy to acquire an S2 graft - A. R. Monakhov; V. R. Salimov; S. V. Meshcheryakov; I. I. Kurbanov; D. I. Bystrov; S. V. Gautier (Вестник трансплантологии и искусственных органов, 2025)
Background. Liver transplantation (LT) in children with low body weight using the left lateral segment from a living donor is associated with large-for-size syndrome (LFSS). We present the first Russian clinical case of laparoscopic living-donor hepatectomy to acquire an S2 graft. Materials and methods. A six-month-old child who had biliary atresia-induced liver cirrhosis was prepared for transplantation. The child’s 20-year-old mother was the donor. The left lateral segment had a volume of 426 mL (graft-to-recipient weight ratio, GRWR, was 5.9%). Indocyanine green fluorescence-guided laparoscopic intracorporeal reduction up to the S2 segment was performed. Results. Donor operation time was 230 minutes, blood loss was 50 ml. The postoperative period was uneventful; the donor was discharged on day 9. The recipient had no surgical complications; a rejection episode was successfully managed. The child was discharged with a satisfactory graft function. Discussion. Fluorescenceguided laparoscopic living-donor hepatectomy to acquire an S2 graft is effective and safe. The presented technique may be an effective solution when performing monosegmental LT under the high-risk conditions of LFSS.